Problematic Smartphone Use (PSU) and Learning Outcomes: Learning Motivation as a Mediator - Salsabillah, Excellina; Mohamad Arief Rafsanjani (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Good learning outcomes enable students to develop important skills and knowledge in various fields with learning motivation having a very important role in the learning process, with high motivation it can help students to achieve achievement and With good learning motivation, students will reduce the habit of using smartphones excessively. This research aims to determine the relationship between problematic smartphone use and learning outcomes directly and indirectly through learning motivation. This research uses a quantitative approach, with an ex post facto type of research. The research sample was 288 students at SMA Al-Islam 1 Krian, using random sampling techniques. The measuring instruments used are the SAS-SV scale (10 items), and the SOS scale (10 items). The data analysis used is the Structural Equation Model (SEM) with the Partial Least Square (PLS) equation model in Smart-PLS 4 software. Statistical test results. The results of this research show that: PSU has no significant effect on learning outcomes, PSU has a significant effect on motivation learning, learning motivation does not have a significant effect on learning outcomes, and learning motivation cannot mediate the influence of PSU on learning outcomes.